The level of fundamental qualities of somatic structure and physical fitness of young classical dancers in comparison to their peers practising acrobatic gymnastics – a comparative analysis - Zieliński, Wojciech; Celka, Roman; Adamczyk, Jan; Stanoch, Małgorzata (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Classical (academic) dance, colloquially called ballet, is associated with subtlety and incredible grace of movement. Despite the fact that there has been ages from the creation of ballet, the undoubted beauty and airiness of the forms presented by the dancers make ballet still very popular throughout the world. Ballet is a kind of theatrical show with such fundamental elements as music, choreography and movement. Considering a ballet performance (obviously in a great simplification) and analysing it solely and exclusively within the aforementioned elements, it may be assumed that there is a parallel between the elements of classical dance and an acrobatic routine presented during competitions. Music, choreography and movement are essential in acrobatics as well.The aim of this study is to compare the level of somatic qualities (body height and weight) and the characteristics of fundamental qualities of physical fitness (agility, strength, flexibility, liveliness) of ballet dancers, as well as presenting their results in comparison to dancers’ peers practising acrobatic gymnastics.The results of the analysis indicate that dancers are significantly taller than acrobats also when compared to the standards described in Drozdowski’s „Dzieci Polski Zachodniej”. The adopted assumption of a lower level of general physical fitness of classical dancers in comparison to acrobats has been confirmed. At the same time, in an attempt to measure the flexibility of the body, a statistical difference has been observed within a group of 12-year old girls only.